MOLECULAR TYPING OF MULTI DRUG RESISTANCE E.COLI THAT ISOLATES FROM PATIENT WITH URINARY TRACT INFECTIONS IN NAJAF PROVINCE - Abdulhadi, Ali M Hussein (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aimed to detect the diversity of multidrug-resistant Escherichia coli strains isolated from urinary tract infection (UTI) patients and to assess their potential for biofilm formation. Method: Twenty bacterial isolates were obtained from urine cultures of UTI patients hospitalized at Najaf Teaching Hospital. The isolates were cultured on blood agar and MacConkey's agar, identified using the Vitek 2 system, and subjected to antibiotic susceptibility testing with the AST card. Genetic diversity among the isolates was further analyzed using ERIC-PCR. Results: The findings revealed high levels of antibiotic resistance among the E. coli isolates: 100% resistance to amoxicillin and ampicillin, 90% to ceftriaxone and ceftazidime, 70% to amikacin, and 55% to meropenem. ERIC-PCR results demonstrated genetic variation among isolates, which were grouped into five distinct clusters with similarity indices ranging from 40% to 90%. Novelty: This study provides insight into the alarming resistance patterns and genetic diversity of uropathogenic E. coli, underlining the critical need for tailored antibiotic stewardship and further investigation into their biofilm-forming capabilities in clinical settings.